Brachioradial pruritus in a young man presenting with transverse myelitis - Jui-Hung Ko; Po-Yu Shih; Yu-Huei Huang (Wolters Kluwer Medknow Publications, 2010)
Pruritus with unknown origin is a common complaint and secondary causes should be investigated. We report a 22-year-old man with intractable localized pruritus and painful burning, stinging sensations in the bilateral arms, shoulders, neck and upper back for 3 weeks. A dermatologist was consulted in the emergency department. On physical examination, there were multiple excoriated erythematous macules and depigmented scars in a linear distribution over the dermatome from C4 to C6. Decreased muscle power in bilateral upper limbs was also noted. A consultant dermatologist strongly suggested that an image survey on the cervical spine was necessary. Surprisingly, a magnetic resonance image (MRI) of the cervical spine revealed a lesion with T1 hypointensity and T2 hyperintensity occupying two-thirds of the intramedullary region at the C2-C5 levels, consistent with transverse myelitis. Brachioradial pruritus with transverse myelitis was diagnosed. It is important for clinicians to be aware that bra-chioradial pruritus should be a differential diagnosis of pruritus of unknown origin and that the disease entity is not responsive to systemic corticosteroids and antihistamines; however, it is dependent on treatment of the underlying process. Once the diagnosis of brachioradial pruritus is made, plain film or MRI of the cervical spine should be arranged to determine the presence of possible nerve compression lesions.